Professional Pathways for Musicians with Disability in Victoria, Australia. Issue 1 (2nd January 2022) - Skinner, Anthea; Thompson, Grace; Skewes McFerran, Katrina
Abstract: The work of disabled musicians has become the focus on of an increasingly large body of academic work; however, existing literature rarely provides details about the educational experiences of these musicians, or how disability impacted these experiences. This study interviewed eleven performing musicians living with disability in Australia to elucidate the barriers and enablers that they faced in their music educations and careers. We developed a 'nested model' based on a qualitative narrative analysis which identified barriers and enablers coming from 'the musician', 'the self', 'other people', and 'the system'. We used this model to draw out further themes and counter-themes across the interviews to begin to illuminate the barriers. Each of our participants was able to identify numerous barriers to access, which they had experienced during their musical careers. Despite this, ten of our eleven participants continued to find ways to participate and express their creativity in musical activities, and they provided many practical suggestions for improving access. Future studies that seek perspectives from disabled music students, or those who are in the early stages of their careers, may provide further insights to better understand barriers and enablers.